POSTTRAUMATIC STRESS DISORDER– A SYSTEMATIC OVERVIEW IN NEW DIAGNOSIS AND TREATMENT APPROACHES - Pejuskovic, Bojana (Medical Research, 2024)
Posttraumatic stress disorder (PTSD) is a complex condition, common and disabling psychiatric disorder that causes incalculable suffering for millions of people. It is associated with a high rate of functional impairment, somatic complaints, risk of suicide and comorbid psychiatric disorders, as well as extraordinary costs for health care system. A diagnosis of PTSD requires evidence of exposure to trauma, and is characterized by symptoms of re-experiencing, avoidance, and changes in arousal and reactivity. The American classification system added another cluster of symptoms related to negative changes in cognition and mood related to trauma, while the European classification system added complex PTSD as a new diagnosis. No evidence supported any one intervention as a universal prevention strategy. CBT-TF, CBT and EMDR treatment had a positive effect. Psychotherapy is the first line of choice in the treatment of PTSD. Trauma-focus interventions are recommended: CBT-TF, PE and EMDR, as well as stress management therapy. Pharmacotherapy approaches should start with one of the first-line options that include an SSRI such as fluoxetine, paroxetine or sertraline, or the SNRI venlafaxine. Research evaluating combined psychological and pharmacological treatments for PTSD is limited and requires further study, but certain forms of PTSD require an integrative and multidisciplinary approach. Prevention, early detection and clear treatment guidelines could be the best choice for every traumatized person as well as for the health care system. Key words: posttraumatic stress disorder, traumatic experiences, diagnosis, pharmacotherapy, psychotherapy